Analysis of reaction products formed in the gas phase reaction of E, E-2, 4-hexadienal with atmospheric oxidants: Reaction mechanisms and atmospheric implications. (March 2018) - Colmenar, I.; Martin, P.; Cabañas, B.; Salgado, S.; Martinez, E.
Abstract: An analysis of reaction products for the reaction of E, E-2, 4-hexadienal with chlorine atoms (Cl) and OH and NO3 radicals has been carried out at the first time with the aim of obtaining a better understanding of the tropospheric reactivity of α, β-unsaturated carbonyl compounds. Fourier Transform Infrared (FTIR) spectroscopy and Gas Chromatography-Mass Spectrometry with a Time of Flight detector (GC-TOFMS) were used to carry out the qualitative and/or quantitative analyses. Reaction products in gas and particulate phase were observed from the reactions of E, E-2, 4- hexadienal with all oxidants. E/Z-Butenedial and maleic anhydride were the main products identified in gas phase. E-butenedial calculated molar yield ranging from 4 to 10%. A significant amount of multifunctional compounds (chloro and hydroxy carbonyls) was identified. These compounds could be formed in particulate phase explaining the ∼90% of unaccounted carbon in gas phase. The reaction with Cl atoms in the presence of NOx with a long reaction time gave Peroxy Acetyl Nitrate (PAN) as an additional product, which is known for being an important specie in the generation of the photochemical smog. Nitrated compounds were the major organic products from the reaction with the NO3 radical. Based on the identified products, the reaction mechanisms have been proposed. In these mechanisms a double bond addition of the atmospheric oxidant at C4/C5 of E, E-2, 4-hexadienal is the first step for tropospheric degradation. Highlights: Reaction mechanisms of E, E-2, 4-hexadienal with Cl, OH and NO3 were investigated. E-butenedial was the main product detected for the reactions of E, E-2, 4-hexadienal. Organic nitrated compounds have been detected in reaction with NO3 radical. Unidentified multifunctional compounds in particulate phase were observed. Addition of oxidants at double bond C4/C5 of E, E-2, 4-hexadienal has been proposed.